Catalysts for Monooxygenations Made from Polyoxometalate: An Iron(V)−Oxo Derivative of the Lindqvist Anion - Derat, Etienne; Kumar, Devesh; Neumann, Ronny; Shaik, Sason (Inorganic chemistry, 2006)
This work uses density functional calculations to design a new high-valent Fe(V)O catalyst [Mo5O18FeO]3-, which is based on the Lindqvist polyoxometalate (Mo6O19 2-). Because the parent species is stable to oxidative conditions, one may assume that the newly proposed iron−oxo species will be stable, too. The calculated Mössbauer spectroscopic data may be helpful toward an eventual identification of the species. The calculations of C−H hydroxylation and CC epoxidation of propene show that, if made, [Mo5O18FeO]3- should be a potent oxidant that will be subject to strong solvent effect. Moreover, the Lindqvist catalyst leads to an intriguing result; the reaction that starts along an epoxidation pathway with CC activation ends with a C−H hydroxylation product ( 46) due to rearrangement on the catalyst. The origins of this result are analyzed in terms of the structure of the catalyst and the electronic requirements for conversion of an epoxidation intermediate to a hydroxylation product. Thus, if made, the [Mo5O18FeO]3 will be a selective C−H hydroxylation reagent.